PENGARUH DOCOSAHEXAENOIC ACID (DHA) PADA TUMBUH KEMBANG ANAK BALITA GIZI BURUK YANG DIRAWAT JALAN [The effect of DocosaHexaenoic Acid (DHA) on growth and development of outpatient rehabilitation of children under-five with severe malnutrition] - Astuti Lamid; Susi Suwarti; Sihadi ,; Lies Karyadi; Paul Matulessy; Komari . (Jurnal Teknologi dan Industri Pangan, 2002)
The study examined the effect of DocosaHexaenoic Acid  (DHA) on growth and development of outpatient rehabilitation of children under five with severe malnutrition. Sample was children whose age from 6 to 24 months suffering from severe malnutrition with weight /age index  of WHO standard  of Z score <-3,0 standard deviation (SD) . The total samples (n=44) were admitted followed the study completely 44. Then, they were grouped randomly into two groups namely : DHA group and control group which each group consists of 22 children. DHA group will be given a packet of outpatient rehabilitation plus DHA whereas control group will be given a packet of outpatient rehabilitation only. Intervention will be given for 3 months. The packet of outpatient rehabilitation consists of treatment of infectious disease, nutrition extension and 200 gram skimmed  milk powder for a week  as food supplement. DHA dose given was about 60 mg/day. DHA will be added into skimmed milk powder. Data was collected in the beginning and the end of study were: body weight, height, clinical examination, daily food consumption, mental development index (MDI)  psychomotor development index (PDI). The increment of body weight after 3 months intervention of the DHA group was 0,7 kg compared to control group was 0,5 kg. No significant differences were found in the increment of body weight between two groups. The score of MDI and  PDI of DHA group increased after 3 months intervention but statistical analysis showed there were  no significant differences in the increment of MDI and PDI between two groups (p>0,05).